2016
DOI: 10.1111/dewb.12133
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Prohibition of Gestational Surrogacy in Sunni Islam

Abstract: Advances in reproductive medicine have provided new, and much needed, hope for millions of people struggling with infertility. Gestational surrogacy is one such development that has been gaining popularity with infertile couples, especially those unable to benefit from other reproductive procedures such as In Vitro Fertilization. For many Muslim couples, however, surrogacy remains a nonviable option. Islamic scholars have deemed the procedure incompatible with Islam and have prohibited its use. This paper exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…A comparable trend was reported by another Jordanian study showing that religion was a fundamental determinant of attitude toward surrogacy (21). The preservation of lineage, the exclusion of third parties in reproduction, the upholding of the child's rights, and the protection from the negative effects of surrogacy are the major reasoning in prohibiting surrogacy in Muslim Sunni community (20,29). One of the fundamental principles in Sunni Islam is protecting the family lineage.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A comparable trend was reported by another Jordanian study showing that religion was a fundamental determinant of attitude toward surrogacy (21). The preservation of lineage, the exclusion of third parties in reproduction, the upholding of the child's rights, and the protection from the negative effects of surrogacy are the major reasoning in prohibiting surrogacy in Muslim Sunni community (20,29). One of the fundamental principles in Sunni Islam is protecting the family lineage.…”
Section: Discussionsupporting
confidence: 67%
“…For example: 1) a Swedish study demonstrated that 63 of physicians were positive or neutral toward altruistic surrogacy being introduced in Sweden (26), 2) a Romanian study showed that 78 of physicians had high acceptance of ARTs including surrogacy (27), and 3) a British study found that 72 of medical students considered surrogacy as an acceptable form of assisted reproduction (28). Religion seems to play an important role in determining the attitude toward this and similar issues; since 71.7 of participants referred to religion as the source of their attitude (20,29). A comparable trend was reported by another Jordanian study showing that religion was a fundamental determinant of attitude toward surrogacy (21).…”
Section: Discussionsupporting
confidence: 65%
“…Parenthood carries high social value in Muslim societies [4,24,25] and is often tied to an individual's self-perception of manhood or womanhood [3,26,27]. In a pronatalist society, infertility essentially becomes a "social crisis," [3,5] accompanied by substantial distress and stigma for both men and women [11,26,28,29]. The stigma associated with infertility may sometimes lead infertile couples to keep their infertility-and its treatment--a secret [10,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…While the majority of Muslim scholars do not allow surrogacy due to the mixing of nasab and the resulting unclear status of the child's lineage, some scholars (mainly of the Twelver Shia school) allow surrogacy in case the surrogate mother and the egg donor are married to the intended father. 42,44,47 The question of the establishment of motherhood, however, remains. Does the surrogate child in this case have two mothers, a genetic and a birth mother?…”
Section: Scenario Two: Surrogate Motherhood and How It Affects The Rumentioning
confidence: 99%